Market power and spatial price discrimination in the liquefied natural gas industry - Nahim Bin Zahur (Queen's University, Department of Economics, 2023)
The liquefied natural gas (LNG) industry is characterized by systematic inter-regional price differentials, raising the question of whether sellers price discriminate. This paper measures market power in the LNG spot market and studies how market power influences pricing, trade and welfare. I develop a novel method for inferring market conduct that utilizes information on sellers' pricing and quantity decisions across multiple geographically segmented markets. My test for market conduct is based on the observation that sellers exercising market power engage in third-degree price discrimination, whereas sellers behaving competitively do not. Using data from 2006 to 2017 on spot market trade flows, spot prices, shipping costs and seller capacities, I estimate a structural model of LNG trade and pricing that incorporates spatial differentiation, capacity constraints and trade frictions and flexibly nests different models of seller market power. I find that seller decisions are consistent with a Cournot model and unlikely to be generated by a competitive model. The total deadweight loss from market power is estimated to be USD 12 billion, or about 4.5% of total revenue. I find that market power plays a key role in exacerbating inter-regional price differentials.
Keywords: D23; L13; D43; Q41; 330; Market Power; Price Discrimination; Conduct Parameter; Contracts; Liquefied Natural Gas